Relationship between bone turnover markers and diabetic kidney disease in patients with type 2 diabetes - Men, Xueyan; Yue, Peipei; Hao, Weiwei; Zhang, Lei; Chen, En; Liu, Jing (Frontiers in Endocrinology, 2025)
ObjectiveDiabetic kidney disease (DKD) is one of the most serious complications of type 2 diabetes mellitus (T2DM), and bone metabolism disorders show a close linkage to DKD. Thus, this study aimed to explore the association between bone turnover markers (BTMs) and DKD.MethodsIn present cross-sectional study, serum BTMs were detected in 1433 hospitalized patients with T2DM. Logistic regression analysis was used to investigate the associations between osteocalcin (N-MID), β-cross-linked C-telopeptide (β-CTX), total type I collagen N-terminal propeptide (PINP), and the risk of DKD.ResultsThe circulation N-MID, β-CTX, and PINP levels were significantly lower in the DKD group compared with the non-DKD group (all P < 0.05), especially in male and aged < 60 subgroups. Serum BTM levels showed a weak correlations with certain glucose metabolism parameters–such as glycated hemoglobin, fasting blood glucose, C peptide, and fasting insulin−as well as alkaline phosphatase (ALP) levels and low-density lipoprotein (all P < 0.001). A weak negative correlation was also observed with the duration of diabetes (all P < 0.0001). In addition, β-CTX levels showed a minimal positive correlation with eGFR (r = 0.057, P=0.036) and a modest correlation with ALP (r = 0.31, P < 0.0001). After adjusting for potential confounders, higher serum β-CTX levels were independently associated with a lower risk of DKD. However, no significant associations were found among serum N-MID, PINP, and the risk of DKD.ConclusionBTM levels were significantly decreased in patients with DKD. Lower β-CTX levels were independently associated with a larger prevalence of DKD after adjusting for potential confounders, suggesting that serum β-CTX may be an independent marker associated with the risk of DKD.